Primary Mucosal Melanoma of the Stomach. (12th August 2018) - Phillips, O.; Higdon, A.; Colaco, R.; Fish, H.
Abstract : Considered to be rare, mucosal melanomas are rare type of melanoma that are found on mucosal surfaces and are primary or metastatic in origin. We report a case of a 66-year-old Hispanic female who presented with vague abdominal pain and upon further endoscopic work-up revealed 2 gastric lesions. Endoscopic biopsy results revealed gastric melanoma in the distal lesion. A PET/CT scan indicated it to be suspicious for the primary site of metastasis but was ultimately diagnosed as a benign nevus on biopsy. An extensive clinical exam showed no other probable sites of origin. The patient underwent a subtotal Billroth II gastrectomy and enterostomy tube placement for temporary feeding. Primary melanoma of the stomach is an exceptionally rare occurrence with limited cases that can be accounted for in literature; thus we report this case for review.